Adaptabilitas Varietas Inpara di Lahan Rawa Pasang Surut Tipe Luapan Air B pada Musim Kemarau - ,, Koesrini; Saleh, Muhammad; Nurzakiah, dan Siti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Tidal swamp lands are marginal lands with considerable potentials for rice farming. The key solution to overcome swampy lands constraints are nutrient and water managements as well as the use of adaptive rice varieties. Inpara (inbred swampy land rices) varieties have been released by the Indonesian Agency for Agricultural Research and Development (IAARD) which are adaptive to swampy land conditions. The purpose of this research was to evaluate the adaptability of Inpara varieties in tidal swamp lands with type B overflow. The field experiment was carried out in Karang Bunga village, Barito Kuala District, South Kalimantan Province, in the dry season from April to August 2016. The research was arranged in randomized complete block design, with 3 replicates. The varieties tested, i.e., Inpara 1, 2, 3, 4, 5, 6, 7, 8, 9, and check varieties Margasari, Ciherang, and Mekongga. The results showed that the adaptability varied among varieties tested. Inpara 3, 4, 6, 8, and 9 had high yield and good adaptation on tidal swamp land yielded 3.475-4.299 ton ha-1. These varieties produced between 38.5 to 71.3% higher than Margasari and 51.4 to 87.2% higher than Mekongga. Inpara 3, 4, 6, 8, and 9 could be used as a main varieties in the tidal swamp lands.Keywords: rice, swampy land, variety